AI-Gamification in Qur’anic Learning: Assessing Indonesian Islamic Religious Education Teachers’ Readiness for Generation Alpha - Artha Nugraha, Nursani Awal; Firmansyah, Mokh. Iman; Nugraha, Risris Hari (TARBIYA: Journal of Education in Muslim Society, 2025)
AbstractThis study investigates the readiness of Indonesian Islamic Religious Education (PAI) teachers at the lower secondary level to integrate AI-based gamification into Qur’anic learning for Generation Alpha students. As part of the Transformative Tilawah research program, the study also provides initial validity evidence for the TRAIGE instrument, which measures five dimensions of readiness: technical, pedagogical, content, perceived usefulness, and institutional readiness. Using a convergent mixed-methods design, data were collected through a survey of 30 teachers and semi-structured interviews with 5 participants selected through purposive network sampling. Quantitative data were analyzed descriptively, while qualitative data were examined using reflexive thematic analysis. The findings show that overall teacher readiness is high (M = 81.50; 81.5%). Technical readiness is the strongest dimension (87.2%), whereas pedagogical readiness is the weakest (78.9%). Perceived usefulness is very high (82.0%), indicating positive views of AI-gamification for motivation and learning outcomes. However, a support-capacity gap persists: leadership is supportive, but training and technical assistance remain limited. Implementation therefore requires ethical design, pedagogical strengthening, and stronger institutional support.   AbstrakPenelitian ini mengkaji kesiapan guru Pendidikan Agama Islam (PAI) tingkat SMP di Indonesia dalam mengintegrasikan gamifikasi berbasis AI ke dalam pembelajaran Al-Qur’an bagi Generasi Alpha. Sebagai bagian dari program riset Transformative Tilawah, studi ini juga memberikan bukti validitas awal terhadap instrumen TRAIGE yang mengukur lima dimensi kesiapan, yaitu kesiapan teknis, pedagogis, konten, persepsi kegunaan, dan dukungan institusional. Penelitian menggunakan desain mixed methods konvergen dengan pengumpulan data melalui survei terhadap 30 guru serta wawancara semi-terstruktur dengan 5 partisipan yang dipilih melalui purposive network sampling. Data kuantitatif dianalisis secara deskriptif, sedangkan data kualitatif dianalisis menggunakan reflexive thematic analysis. Hasil penelitian menunjukkan bahwa kesiapan guru secara umum berada pada kategori tinggi (M = 81,50; 81,5%). Kesiapan teknis menjadi dimensi terkuat (87,2%), sedangkan kesiapan pedagogis menjadi yang terendah (78,9%). Persepsi kegunaan berada pada kategori sangat tinggi (82,0%). Namun, masih terdapat kesenjangan antara dukungan pimpinan dan kapasitas nyata sekolah, terutama dalam pelatihan dan bantuan teknis. Karena itu, implementasi memerlukan desain etis, penguatan pedagogis, dan dukungan institusional yang lebih kuat.